The Public Health Surveillance Well-Being Scale: Reliability and validity study of the Turkish version - Selma Infal Kesim; Fatih Kara (Journal of Health and Social Sciences)
Introduction: The Public Health Surveillance Well-Being Scale (PHS-WB) is a measuring tool developed by Bann and colleagues (2012) for determining the well-being status of a community, expressed in terms of physical, mental, and social well-being. This study aimed to adapt, translate and validate the PHS-WB from English into the Turkish language. Methods: A questionnaire ad hoc for collecting socio-demographic characteristics of participants, the Public Health Surveillance Well-Being Scale (PHS-WS) and the Perceived Wellness Scale (PWS) were used in our study. For the validity of the PHS-WS language, the original language of the scale was first translated from English into Turkish, whereas the back translation of the final draft was carried out from Turkish to English by a different language expert. The Content Validity Index was calculated. For the scale (criterion) validity, the coincidental scale validation method was used. The structural validity was assessed by using the exploratory factor analysis (EFA). Results: The scale showed a high internal consistency, as the Cronbach’s alpha coefficient was 0.83 for the total score and 0.66, 0.76, and 0.69 for the physical, social and mental subscales, respectively. There was a total of 12 items in the final Turkish form of the PHS-WB, having the same factor structure as the original as result of the validity and safety studies performed. Discussion and Conclusions: The validity and reliability of the Public Health Surveillance Well-being Scale was ensured. This questionnaire could be used by researchers for further investigation in different regions of Turkey, on larger sample groups and for evaluation of special groups, such as individuals with chronic illness and disability, or individuals employed in specific occupation (e.g., healthcare and social care professionals, unemployed, and students).